ANALISIS FAKTOR PEMELIHARAAN MESIN TERHADAP KELANCARAN PROSES PRODUKSI PUPUK DOLOMITE PADA LMC-LIANCO GROUP TAPANULI SELATAN - Rahmat . (Jurnal Education and Development, 2020)
This study aims to determine the extent of the influence of engine maintenance factors on the smooth production process of Dolomite Fertilizer on the LMC-Lianco Group. The research method used in this research is analytical descriptive. As the population in this study were all employees in the dolomite fertilizer production division of 43 people. While the sample in this study was to use a total sampling technique, so the number of samples in the study was 43 people. Analysis of the data used in this study is the technique of multiple linear regression analysis and SPSS version 11.5 for windows. Based on the calculation obtained tcount = 3.094 while ttable with dk = n-2 at α = 0.5% is equal to 2.021 turns out tcount> ttable or 3.094> 2.021 which means that the hypothesis is accepted stating the existence of a significant relationship or influence between machine maintenance (X ) to the smooth production process (Y). The results of the above calculation Rxy = 0.435 is a regression calculation between the variable X (Machine Maintenance) with the Y variable (Smooth Production Process), which means it has a strong relationship level and there is an interval coefficient of 0.40 - 0.599.